Dampak Kearifan Lokal Terhadap Pemilihan Lembaga Gadai Formal Dan Non Formal Pada Masyarakat Desa Bulu Sema Kabupaten Aceh Singkil - Mardiah; Siregar, Friska Anggi; Rizal, Syamsul (Jurnal Samudra Ekonomika, 2024)
One of the local wisdoms in Aceh Singkil is that people still use formal and informal pawn systems. People have the confidence to pawn their goods to relatives or local residents to protect their property to avoid usury. Apart from the public, there are also those who decide to pawn goods with formal pawning. Even though the administration costs are high, the goods being pawned are guaranteed to be safe and the process is official so it is more effective and efficient. So the village has two understandings in choosing pawn products. This research aims to find out how the impact of local wisdom can influence the Bulu Sema Community of Aceh Singkil Regency in choosing formal and non-formal pawn institutions. The research method used is direct field research. Furthermore, the results of this research show that the practice of pawning in the people of Bulu Sema Village, Kab. Aceh Singkil in choosing formal and non-formal pawn institutions is based on the level of knowledge of the relevant community regarding the type of pawn itself. Local wisdom in the people of Bulu Sema District. Aceh Singkil has an impact on choosing formal and non-formal pawn institutions. This is because the source of people's livelihood comes from plantation products. The majority of the community's work as planters has influenced the local wisdom of this village because they mortgaged their garden land.